2009
DOI: 10.1097/mbc.0b013e328329f28c
|View full text |Cite
|
Sign up to set email alerts
|

Elevations in soluble CD40 ligand in patients with high platelet aggregability undergoing percutaneous coronary intervention

Abstract: High aggregatory responses despite antiplatelet treatment is associated with an increased risk of thrombotic complications following percutaneous coronary intervention (PCI). In the present study, we investigated the relationship between platelet aggregatory responses to ADP and the release of CD40L (sCD40L): an immunomodulatory compound involved in atherothrombosis - in patients undergoing PCI. ADP-induced platelet aggregation, sCD40L and soluble P-selectin (sP-selectin) were determined before and 24 h after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Soluble CD40L is a marker of platelet activation, and the majority of sCD40L in the blood is derived from activated platelets 23,24) . It has also been demonstrated that a higher degree of platelet aggregation prior to angioplasty is associated with a greater increase in sCD40L release into the circulation after the procedure 25) . In this study, we observed a statistically significant increase in the sCD40L levels following the cessation of clopidogrel in relation to the values obtained under treatment with clopidogrel.…”
Section: Resultsmentioning
confidence: 99%
“…Soluble CD40L is a marker of platelet activation, and the majority of sCD40L in the blood is derived from activated platelets 23,24) . It has also been demonstrated that a higher degree of platelet aggregation prior to angioplasty is associated with a greater increase in sCD40L release into the circulation after the procedure 25) . In this study, we observed a statistically significant increase in the sCD40L levels following the cessation of clopidogrel in relation to the values obtained under treatment with clopidogrel.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of CD40/CD40L system in monocytes and their activation status in atherosclerosis and cardiovascular events are closely related to each other [6][7][8][9][10]. In this prospective, case-control study of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid up-regulation of CD154 on activated platelets leads to the release of soluble CD154 (sCD40L) and inflammatory response in cells constitutively expressing CD40 [9]. Accordingly, increased platelet activation and elevated levels of CD154 were shown in patients with acute cerebral symptoms, myocardial infarction, and hypercholesterolemic subjects [7][8][9][10][11]. Healthy women with increased plasma levels of soluble CD40L were shown to be at risk for cardiovascular events [12].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 2 more Smart Citations